NICORANDIL MUCOADHESIVE MICROSPHERES: FORMULATION DEVELOPMENT, PHYSICO-CHEMICAL AND FUNCTIONAL CHARACTERIZATION - HADKE, ANKITA V.; PETHE, ANIL M.; KESALKAR, MAHESH A. (International Journal of Applied Pharmaceutics, 2023)
Objective: The study aims to prepare and evaluate Nicorandil mucoadhesive microspheres to improve the oral physicochemical properties of nicorandil and mucoadhesion to extend the residence time at the absorption site. Methods: Nicorandil mucoadhesive microsphere was prepared by emulsion cross-linking method using fenugreek gum, karaya gum as polymer, and glutaraldehyde as a cross-linking agent. Drug entrapment efficiency, particle size, % swelling index, mucoadhesion study, differential scanning calorimetry, powder x-ray diffraction, Fourier transform infrared spectroscopy, and in vitro dissolution studies were used to characterize the microspheres. Results: The characterization studies indicated the formation of mucoadhesive microspheres. The nicorandil mucoadhesive microspheres particle size is130.83±0.48, entrapment efficiency 66.91±0.54, swelling index 82.69±0.40, % mucoadhesion 95.22±0.13 and in vitro drug release was found to be 89.96±0.17 % at the end of 12 h. Conclusion: This research work successfully formed nicorandil mucoadhesive microspheres formulation using the emulsion cross-linking method. Encapsulation efficiency and other physicochemical and functional characterization of microspheres suggested the successful formation of nicorandil mucoadhesive microspheres.